2011
DOI: 10.1002/chem.201101880
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Organoplatinum(II) Complexes with Functionalized Cyclometalated C^N^C Ligands: Structures, Photophysical Properties, and Material Applications

Abstract: A series of [(R'-C^N^C-R'')Pt(L)] complexes with doubly deprotonated cyclometalated R'-C^N^C-R'' ligands (R'-C^N^C-R''=2,6-diphenylpyridine derivatives) functionalized with carbazole, fluorene, or thiophene unit(s) have been synthesized and their photophysical properties studied. The X-ray crystal structures reveal extensive intermolecular π···π and C-H···π interactions between the cyclometalated C^N^C ligands. Compared to previously reported cyclometalated platinum(II) complexes [(C^N^C)Pt(L)], which are non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 70 publications
14
68
0
Order By: Relevance
“…Similar to the case of C^N^N type of ligands, a significant structural distortion is the main factor that accounts for this low emission efficiency. However, Che and co-workers demonstrated that extension of the π-conjugation at the tridentate ligand, together with the use of heterocyclic moieties such as thiophene or carbazole, clearly favours the luminescence properties of these type of platinum(II) complexes [68]. …”
Section: Reviewmentioning
confidence: 99%
“…Similar to the case of C^N^N type of ligands, a significant structural distortion is the main factor that accounts for this low emission efficiency. However, Che and co-workers demonstrated that extension of the π-conjugation at the tridentate ligand, together with the use of heterocyclic moieties such as thiophene or carbazole, clearly favours the luminescence properties of these type of platinum(II) complexes [68]. …”
Section: Reviewmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30] These systems have a strong propensity to aggregate in solution and in the solid state via Pt•••Pt and/or other secondary forces, as recently shown for various classes of complexes in a comprehensive review by Yam and co-workers. 31 Among them, the self-assembly features of hydrophobic Pt(II) complexes with acetylide, [32][33][34][35][36] bidentate, [37][38][39] tridentate N-donor, [40][41][42] and cyclometalating ligands [43][44][45] are relatively well understood. 31 In contrast, their hydrophobic counterparts featuring non-chelating ligands and, in particular, bis(pyridyl) Pt(II) complexes have been limited to liquid crystalline materials [46][47][48] and hydrogen-bonded metallogelators.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the fact that cis configuration of the platinum precursor is not required comes from the fact that double cyclometallation of 3,6-bis(2-thienyl)-1,2,4,5-tetrazine has been achieved from the precursor trans-[Pt (2,4,6-Me 3 C 6 H 2 ) 2 (dmso) 2 ] in a reaction leading to a dinuclear platinum(II) compound [55]. [60] in order to compare the results with those obtained when [Pt 2 Me 4 (μ-SMe 2 ) 2 ] was used as precursor.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclometallated platinum compounds containing N-donor ligands have attracted a great deal of attention because of their potential interest in both areas [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For this reason, the development of new methods for the preparation of cycloplatinated compounds containing N-donor ligands is a pursued goal.…”
Section: Introductionmentioning
confidence: 99%